Power systems and electromagnetic safety in of powerful utility buildings and structures - Запорожець, О.І.; Глива, В.А.; Клапченко, В.І.; Потапенко, Г.Д.; Лук’янчиков, А.В. (Proceedings of National Aviation University, 2008)
Researching of origin terms of electromagnetic contaminations from the unbalanced currents and leak currents in the industrial networks of electric supply of structures and buildings saturated energy.